Phytoaccumulation of Zn, Pb, and Cd in Conocarpus lancifolius irrigated with wastewater: does physiological response influence heavy metal uptake?. Issue 3 (23rd February 2020) - Rasheed, Fahad; Zafar, Zikria; Waseem, Zulfiqar Ali; Rafay, Muhammad; Abdullah, Muhammad; Salam, Mir Md Abdus; Mohsin, Muhammad; Khan, Waseem Razzaq
Abstract: Conocarpus lancifolius is a fast-growing and drought tolerant tree species with phytoremediation potential in arid environments. The present study was conducted to evaluate the phytoaccumulation potential under wastewater treatment. The experiment was performed in a greenhouse where 3-month-old seedlings were irrigated with industrial wastewater and growth, biomass and physiological parameters were measured. Concentrations of zinc (Zn), lead (Pb), and cadmium (Cd) in leaves, shoots, and roots along with translocation and tolerance index were also determined. The results showed that under wastewater treatment total biomass increased from 24.2 to 31.5 g, net CO2 assimilation rate increased from 9.93 to 13.3 μmol m −2 s −1, and water use efficiency increased from 1.7 to 2.42. Similarly, heavy metals (Zn, Pb, and Cd) accumulation in stem, leaves, and roots increased significantly under wastewater treatment where the highest concentration of Zn, Pb and Cd was found in roots followed by leaves and stem, respectively. Tolerance index was found >1, and translocation factor of all heavy metals was found >1. The study revealed that phytoaccumulation potential of C. lancifolius was mainly driven by improved net CO2 assimilation rate and water use efficiency.